Przyczynek do badań nad stylem uradzkim w zachodniej Wielkopolsce na przykładzie materiałów z cmentarzyska w Wartosławiu, pow. szamotulski - Mizerka, Jagoda (Folia Praehistorica Posnaniensia, 2020)
This article presents the issues of the Urad style on the example of ceramics and metal products from the cemetery in Wartosław. The ceramic was obtained in the 19th century as a result of amateur research and in 2009 during archaeological excavations. Findings concerning the definition of the style of Uradzka ceramics and the interpretation possibilities of this phenomenon, registered in western Greater Poland, in the Lubusz region and in eastern Brandenburg, are presented.